2015
DOI: 10.1093/femsle/fnv047
|View full text |Cite
|
Sign up to set email alerts
|

Change in cell surface properties of Lactobacillus casei under heat shock treatment

Abstract: We undertake this study in the aim to give new insight about the change in cellular physiological state under heat shock treatment and probiotic strain screening procedure. Different cell properties have been studied like adhesive ability to biotic and abiotic surfaces, the cell surface hydrophobicity and the fatty acids profiles. Compared to the normal cells, the heated cells increased their adhesive ability to biotic surface. However, the adhesion to abiotic surface was decreased. The cell surface hydrophobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Generally, adhesion is a complex process involving non-specific (hydrophobic interactions between cell surfaces) and specific ligand-receptor interactions [6]. Different structures and specific cell wall components of bacteria, such as fimbriae or pili, adhesins, mucus-binding proteins, fibronectin-binding proteins, or surface layer proteins, provide them an advantage for epithelial colonization; further, lipoteichoic acid or exopolysaccharides produced by bacteria can contribute to adhesion to host epithelial cells [12,13,15,16]. Interactions among all these properties important for adhesion provide the benefit of intestine colonization to probiotic strains.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, adhesion is a complex process involving non-specific (hydrophobic interactions between cell surfaces) and specific ligand-receptor interactions [6]. Different structures and specific cell wall components of bacteria, such as fimbriae or pili, adhesins, mucus-binding proteins, fibronectin-binding proteins, or surface layer proteins, provide them an advantage for epithelial colonization; further, lipoteichoic acid or exopolysaccharides produced by bacteria can contribute to adhesion to host epithelial cells [12,13,15,16]. Interactions among all these properties important for adhesion provide the benefit of intestine colonization to probiotic strains.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that two mechanisms are probably involved in the adhesion of probiotics to gut mucosa: specific adhesion to host intestinal epithelial surfaces (IESM) and unspecific adhesion to hydrophobic surfaces (de Wouters et al, 2015). The first line of contact is the mucus which acts as a protective layer due to its hydrophobic nature, thus the hydrophobicity of bacterial surface could play a significant role favouring the contact with host and promoting the second stage of adhesion by specific cell wall components (Haddaji et al, 2015). Hydrophobicity of cell envelope has been proposed as a simple screening index to test the ability of bacteria or yeasts to adhere to mucosa (Dhewa et al, 2009;Bautista-Gallego et al, 2013;Perricone et al, 2014a;Tokatli et al, 2015;Corbo et al, 2017;Speranza et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…One of the main factors that vary from one Lactobacillus spp. to another is the potential of the strain to resist at high temperatures [ 43 , 44 , 45 , 46 ]. Gunenc et al [ 16 ] reported an increase of 6% in the case where whole sea buckthorn was utilized with a Lactobacillus strain during storage over 14 days in comparison with the sample where no sea buckthorn was added.…”
Section: Discussionmentioning
confidence: 99%